Implementation of Rewards and Punishments in Strengthening Students' Integrity Character in PPKn Learning at MI Al-Hidayah Gesikharjo Tuban - Eka Nur Hidayatin; Akhmad Aji Pradana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the implementation of operant conditioning theory through a reward and punishment system on the integrity character of third-grade students in Civics (PPKn) at MI Al-Hidayah Gesikharjo Tuban in the 2025/2026 academic year. This research employed a quantitative approach with a one-group pretest-posttest design. The research subjects consisted of 20 third-grade students. Data were collected through observation, questionnaires, and documentation. Data analysis was conducted using IBM SPSS Statistics through normality test, homogeneity test, and paired sample t-test. The results showed that the implementation of the reward and punishment system in Civics learning was able to bring positive behavioral changes in students, especially in aspects of discipline, responsibility, and honesty The paired sample t-test showed a significance value of 0.811 > 0.05, indicating that there was no statistically significant difference between the pretest and posttest results. Based on these findings, it can be concluded that the implementation of operant conditioning theory through a reward and punishment system descriptively supports the strengthening of students’ integrity character, but has not shown a statistically significant effect. Therefore, the development of integrity character requires continuous habituation, role modeling, and reinforcement both in the school and family environments.